2014
DOI: 10.1038/ki.2014.46
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T cells and cancer: an undesired tolerance

Abstract: The incidence of cancer is markedly increased in organ transplant patients. A better understanding of underlying mechanisms and the identification of biomarkers for diagnosis and prognosis are major challenges. Hope et al. report expansion of regulatory T cells to be associated with the presence and severity of cancer. Although relevant, these results raise several questions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…This includes changes in the tumour microenvironment and the alteration of immune effector cell sub-populations to influence the global immune response. For example, it has been shown that the proportion of CD4 + regulatory T cells (T Reg cells) both in the peripheral blood and local tumour microenvironment are increased, which is associated with poorer outcomes [4][5][6][7]. Under normal conditions T Reg cells are essential to limit the immune response post-infection and thus prevent host tissue damage.…”
Section: Introductionmentioning
confidence: 99%
“…This includes changes in the tumour microenvironment and the alteration of immune effector cell sub-populations to influence the global immune response. For example, it has been shown that the proportion of CD4 + regulatory T cells (T Reg cells) both in the peripheral blood and local tumour microenvironment are increased, which is associated with poorer outcomes [4][5][6][7]. Under normal conditions T Reg cells are essential to limit the immune response post-infection and thus prevent host tissue damage.…”
Section: Introductionmentioning
confidence: 99%